TAK1 blockade as a therapy for retinal neovascularization. (January 2023) - Wang, Jiang-Hui; Lin, Fan-Li; Chen, Jinying; Zhu, Linxin; Chuang, Yu-Fan; Tu, Leilei; Ma, Chenkai; Ling, Damien; Hewitt, Alex W.; Tseng, Ching-Li; Shah, Manisha H.; Bui, Bang V.; et al.
Abstract: Retinal neovascularization, or pathological angiogenesis in the retina, is a leading cause of blindness in developed countries. Transforming growth factor-β-activated kinase 1 (TAK1) is a mitogen-activated protein kinase kinase kinase (MAPKKK) activated by TGF-β1 and other proinflammatory cytokines. TAK1 is also a key mediator of proinflammatory signals and plays an important role in maintaining vascular integrity upon proinflammatory cytokine stimulation such as TNFα. However, its role in pathological angiogenesis, particularly in retinal neovascularization, remains unclear. Here, we investigate the regulatory role of TAK1 in human endothelial cells responding to inflammatory stimuli and in a rat model of oxygen-induced retinopathy (OIR) featured retinal neovascularization. Using TAK1 knockout human endothelial cells that subjected to inflammatory stimuli, transcriptome analysis revealed that TAK1 is required for activation of NFκB signaling and mediates its downstream gene expression related to endothelial activation and angiogenesis. Moreover, pharmacological inhibition of TAK1 by 5Z-7-oxozeaenol attenuated angiogenic activities of endothelial cells. Transcriptome analysis also revealed enrichment of TAK1-mediated NFκB signaling pathway in the retina of OIR rats and retinal neovascular membrane from patients with proliferative diabetic retinopathy. Intravitreal injection of 5Z-7-oxozeaenol significantly reduced hypoxia-induced inflammation and microglial activation, thus attenuating aberrant retinal angiogenesis in OIR rats. Our data suggest that inhibition of TAK1 may have therapeutic potential for the treatment of retinal neovascular pathologies. Graphical Abstract: ga1